Verificação do potencial de uso de resíduos siderúrgicos provenientes de diferentes etapas do processo de refino do aço como agregados em misturas asfálticas do tipo SMA - Azeredo, Leidyanne De Bortoli (2018)
SMA (Stone Matrix Asphalt) concrete, widely used in developed countries, is an interesting alternative of floor covering. However, due to the high interaction between the aggregates, the mixture of the SMA type requires the use of aggregates with characteristics that are not always available in the Brazilian natural reserves, being one of the main resistance to abrasion, which should be less than 30%. Given its proven mechanical strength, the use of the steel aggregate may be an alternative to the SMA blends design. Thus, the objective of this work was to evaluate the potential of using steel aggregates in the composition of asphalt mixtures of the SMA type. The methodology of the research promoted an evaluation of the physical, chemical, mineralogical, morphological and mechanical characteristics of the natural and steel aggregates used as well as the mechanical characterization of SMA mixtures, through a Marshall stability and creep test, diametral compression tensile strength, damage by inhaled moisture, modulus of resilience and abrasion resistance. SMA was determined by varying the percentage of steel aggregates in the composition (30% and 50%), the grain size range (TMN 19mm and TMN 16mm) according to American and German standards, the type of filler material (natural filer and steel filer of KR) and the use of cellulose fiber. From the results of the tests it was concluded that the steel aggregate in SMA mixes meets the requirements of the standards used. The dosage results showed that the use of KR filer or fiber promotes a positive correlation between void volume and increase in VMA, VCA and Marshall Stability. The results showed that the use of 50% steel aggregate allows a considerable improvement in the physical and mechanical behavior of the SMA mixtures. In addition to the technical advantages, the use of steel aggregates provides environmental gain, reducing the deposition of solid waste in the environment and minimizing the extraction of non-renewable natural resources